High energy emissions from thunderstorms: HEETs, from photons to neutrons toward the ground - Gabriel Sousa Diniz (2016)
Thunderstorms are the starting point of several intense phenomena such as gamma rays and X rays, neutron, positron and electron emissions. The X rays and gamma rays have energies that may reach 100 MeV. The neutron emissions may be created by energetic gamma ray photons interacting with the air via Giant Dipole Resonance, a photonuclear reaction, related to thunderstorms and lightning in a way that is not completely understood yet. In this work neutrons were assumed to be created by gamma ray photons in the energy range of 10-30 MeV emitted by leader discharges. Their production and propagation toward the ground were investigated using computer simulations. Cross sections data banks were analyzed to provide estimations on the neutrons creation probability. The analysis revealed that the probability per collision of a photonuclear occurs varies between 0 and 3.2% through the energy range of 10 and 30 MeV. The photons mean free path within this energy range was analyzed together with the atmospheric density profile showing that for photon source altitudes above 1 km, the photons with this energy pass through a sufficiently high number of mean free path to ensure a collision. The free software EGS5 was used to treat the photons and electrons motion through the atmosphere in the intent of analyze the spread of the beams, that were assumed to be monodirectional. The photon beam presented an aperture of 2-6$^{o}$ $±$ 2$^{o}$ while the electron beam was broader showing an aperture of 11-13$^{o}$ $±$ 3$^{o}$. Since EGS5 does not take into account neutron production and motion, the neutron analysis was done with the FLUKA software simulating a photon beam in different initial heights and estimating the photon and neutron ground detection. FLUKA simulations have shown that neutrons are distributed at the ground within a radius of 2 km away from the source axis. The neutrons reached ground with a rate of 10$^{-4} $-10$^{-2}$ neutrons per gamma, which agrees with the cross section analysis done upon the neutron production. The neutron number decrease was used to estimate an upper limit of 5 km for the altitude of a punctual photon source that is capable of generating ground detectable neutrons.